2017
DOI: 10.1016/j.jallcom.2017.06.143
|View full text |Cite
|
Sign up to set email alerts
|

A Kelvin probe force microscopy study of hydrogen insertion and desorption into 2024 aluminum alloy

Abstract: Hydrogen was inserted into 2024 aluminum alloy by cathodic polarization in sulfuric acid at 25 C. Scanning Kelvin Probe Force Microscopy (SKPFM) measurements performed perpendicularly to the charging side revealed a potential gradient and confirmed the insertion of hydrogen over hundreds of microns. A hydrogen diffusion coefficient of 1.7 Â 10 À9 cm 2 s À1 was calculated from SKPFM measurements of H-charged samples for different durations. The evolution of the potential gradient during desorption of hydrogen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…Note that the peaks in | i norm | at x~50 μm before heat treatment and at x~300 μm after heat treatment are associated with the presence of intermetallic compounds. Similar changes in the potential gradient were observed using SKPFM after heat treatment [13,14]. This result confirms that the current gradient observed before the heat treatment is due to the presence of H in the material.…”
Section: Hydrogen Desorptionsupporting
confidence: 83%
See 4 more Smart Citations
“…Note that the peaks in | i norm | at x~50 μm before heat treatment and at x~300 μm after heat treatment are associated with the presence of intermetallic compounds. Similar changes in the potential gradient were observed using SKPFM after heat treatment [13,14]. This result confirms that the current gradient observed before the heat treatment is due to the presence of H in the material.…”
Section: Hydrogen Desorptionsupporting
confidence: 83%
“…The potential gradient was observed at a similar distance as for the current gradient, i.e.~400 μm. The potential gradient observed in SKPFM for H-charged AA 2024 samples was confirmed to be due to hydrogen in an independent gas fusion analysis [13], and also in secondary ion mass spectroscopy (SIMS) measurements by Larignon et al [16]. The good agreement between the distances over which the current and potential gradients are observed confirmed that the observed | i ac | increase for small x is due to the presence of hydrogen.…”
Section: Hydrogen Insertionmentioning
confidence: 64%
See 3 more Smart Citations